Sistem Informasi Penjualan Buah Berbasis Web (Studi Kasus: Toko Buah Dika) - Megawati Sinaga (Universitas Labuhanbatu, 2022)
The purpose of writing this final task is to design, analyze, and build a sales information system that can be managed in data management and reporting. In the data collection the authors use the study method library, the interview method and the analysis method. While in the design method the author uses the database draft method, input design, process design, output design, interface design, and algorithm design, while in testing this information system using the Black Box and White Box methods. This research resulted in an effective sales information system that is fully managed by an administrator in controlling all information related to the governance of product data and sales data, Conclusions obtained in this study namely the system is able to improve the effective governance of product data and sales.